2021
DOI: 10.1186/s12889-021-11494-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of pediatric Lead exposure in Tehran; a prospective cross-sectional study

Abstract: Background Ingestion and inhalation are common routes of exposure for lead in humans. Developing countries still have unacceptably high rates of lead toxicity, especially in children. Studies on probable risk factors of lead poisoning in Iranian children are insufficient. In this study, we aimed to evaluate possible environmental factors in children with high blood lead concentrations living in Tehran and neighboring cities. Methods In a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…According to their results, the mean BLC of workers was 24.5 μg/dL, which was higher than the permissible limit. In those studies, the BLCs were higher than the welders described in the present study; this might be due to the higher air pollution in Tehran and Isfahan as populous industrial cities 31,32 . Another cross-sectional study done by Ahmad et al 33 , (2014) to investigate the BLC, and health problems related to lead intoxication in workers of lead-acid battery factory in Bangladesh, which showed that the BLCs were high among workers, and the mean BLC was 65.25 ± 26.66 μg/dL.…”
Section: Discussioncontrasting
confidence: 55%
“…According to their results, the mean BLC of workers was 24.5 μg/dL, which was higher than the permissible limit. In those studies, the BLCs were higher than the welders described in the present study; this might be due to the higher air pollution in Tehran and Isfahan as populous industrial cities 31,32 . Another cross-sectional study done by Ahmad et al 33 , (2014) to investigate the BLC, and health problems related to lead intoxication in workers of lead-acid battery factory in Bangladesh, which showed that the BLCs were high among workers, and the mean BLC was 65.25 ± 26.66 μg/dL.…”
Section: Discussioncontrasting
confidence: 55%
“…The World Health Organization established that there is no safe concentration of Pb 2+ in the blood, as even a low amount of Pb 2+ has been related to cognitive impairment, particularly in children [4][5][6]. This heavy metal can enter the organism by ingestion, inhalation, and absorption, and once inside, it is distributed to the organs and stored in the teeth and bones [7][8][9][10][11][12]. The central nervous system (CNS) is a target of Pb 2+ toxicity, leading to long-term consequences [5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Ahangar et al [ 61 ] focused on lead exposure from multiple sources. This study was conducted on some children living around industrial areas in Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…Their blood samples revealed that these children were exposed to lead at concentrations far higher than the Environmental Protection Agency (EPA) guidelines. Furthermore, the authors reported that these children were exposed to lead from various routes such as scratched wall paint, house floor dust, windowsill dust, tap water, and consumption of spices [ 61 ].…”
Section: Introductionmentioning
confidence: 99%